1986
DOI: 10.1080/02134748.1986.10821542
|View full text |Cite
|
Sign up to set email alerts
|

Conflicto, Identificacion y Poder en la Influencia Minoritaria

Abstract: ResumenEn 6 condiciones experimentales se presenta a los sujetos un texto minoritario extremamente favorable al aborto, siendo evaluada la influencia en una dimensión directa (actitud frente al aborto) y en una dimensión indirecta (actitud frente a la contracepción). En tres condiciones se introduce una pequeña amenaza y en las otras tres una fuerte amenaza que implica un fuerte costo social simbólico en caso de un eventual acuerdo con la minoría. En cada caso, o bien no se explica ninguna identificación (cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
2
0
3
Order By: Relevance
“…Es decir, desde una perspectiva ecológica como la de Bronfenbrenner (1979), la identidad no se ubicaría solo dentro del sujeto o fuera de él (en la sociedad), sino más bien en el interfaz de ambos subsistemas. La identidad es necesariamente un fenómeno construido socialmente (Ibáñez, 2001(Ibáñez, , 2003Montero, 2002;Mugny, Ibáñez, Elejabarrieta, Iñíguez y Pérez, 1986).…”
Section: Identidad Siempre Social Y En Movimientounclassified
“…Es decir, desde una perspectiva ecológica como la de Bronfenbrenner (1979), la identidad no se ubicaría solo dentro del sujeto o fuera de él (en la sociedad), sino más bien en el interfaz de ambos subsistemas. La identidad es necesariamente un fenómeno construido socialmente (Ibáñez, 2001(Ibáñez, , 2003Montero, 2002;Mugny, Ibáñez, Elejabarrieta, Iñíguez y Pérez, 1986).…”
Section: Identidad Siempre Social Y En Movimientounclassified
“…Pérez and Mugny (1985) found that if an ingroup minority was associated with negative connotations, an outgroup minority obtained more influence than an ingroup minority. Likewise, although it has been shown that increasing the impression of belonging to a common group with a minority leads to more influence (Mugny & Papastamou, 1982), common membership disrupts conversion when symbolic costs of identification are emphasized (e.g., Mugny, Ibáñez, Elejabarrieta, Iniguez, & Pérez, 1986;Souchet, Tafani, Codaccioni, & Mugny, 2006).…”
Section: Dissociation Theorymentioning
confidence: 99%
“…Within the wide range of intragroup processes most prominent are the lines of research centered on the study of social influence processes (Pérez & Mugny, 1988), especially that dedicated to the analysis of minority influence, with collaborations between Spanish and other European researchers (Clark, Latané, Burgeois, Morales, Moscovici, Mugny, Falomir, & Mucchi, 1995; González & Canto, 1995; Mugny, Ibáñez, Elejabarrieta, Íñiguez, & Pérez, 1986; Pérez & Mugny, 1991).…”
Section: Content Analysis Of Small Group Researchmentioning
confidence: 99%